2013
DOI: 10.1016/j.molcel.2013.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways Differentially Affect RNA Polymerase II Initiation, Pausing, and Elongation Rate in Cells

Abstract: On page 216 of the above article, we inadvertently used the wrong sign for one of the constants in the equation representing the steady-state relationship between Pol II density and mRNA levels shown in the main text. The correct equation, which was presented in the Supplemental Materials and is shown below, was used for all related analyses. ½R = 1:77 3 10 À5 ½G 2 + 1:21½G v Our error in no way changes any of our conclusions. We apologize for any inconvenience we may have caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 0 publications
2
57
2
Order By: Relevance
“…This finding begs the question of whether physiological regulation of elongation rate exerts a significant influence on alternative splicing. In favor of this possibility, elongation rates vary between genes and within genes (Danko et al 2013;Jonkers et al 2014;Veloso et al 2014) over a range (;0.5-4 kb/min) that overlaps the average rates of the slow C4/R749H and fast E1126G mutants used here (0.5-1.9 kb/min) ( Fig. 1D; Supplemental Fig.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This finding begs the question of whether physiological regulation of elongation rate exerts a significant influence on alternative splicing. In favor of this possibility, elongation rates vary between genes and within genes (Danko et al 2013;Jonkers et al 2014;Veloso et al 2014) over a range (;0.5-4 kb/min) that overlaps the average rates of the slow C4/R749H and fast E1126G mutants used here (0.5-1.9 kb/min) ( Fig. 1D; Supplemental Fig.…”
Section: Discussionmentioning
confidence: 84%
“…2A). Furthermore, elongation rates have been reported to change in response to physiological stimuli (Danko et al 2013) that could thereby regulate alternative splicing. Intriguingly, many elongation ratesensitive cassette exons in our HEK293 cell lines are also abnormally included or skipped in breast and ovarian tumors (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were collected at ∼70%-80% confluence, and nuclei were isolated as described previously (Luo et al 2014). Nuclear run-on and GRO-seq library preparation were performed as previously described (Hah et al 2011), with modifications (Danko et al 2013;Luo et al 2014). After library quality control assessment using a Bioanalyzer (Agilent), the samples were subjected to 50-bp single-end sequencing using an Illumina HiSeq 2000 Sequencing System.…”
Section: Global Run-on Sequencing (Gro-seq)mentioning
confidence: 99%
“…We can hypothesize that this might be a crucial region for the dystrophin transcriptional dynamics regulation, requiring a pausing site and then restarting elongation downstream. Since R-loops also promote chromatin architecture shaping, which controls termination region, this region might also be implicated in gene transcription termination and polyadenylation regulation [32,33]. Very recently ultra-deep transcript sequencing analyses have shown that dystrophin pre-mRNA undergoes multi-step non-sequential splicing thus suggesting a highly regulated process in which control of RNA pol II processivity may be critical [34].…”
Section: A New Dmd Rna Pol II Pausing Sitementioning
confidence: 99%